Tính
A=2^2010-(2^2009+2^2008+...+2^1720)
tính 2010*2010-2009*2009+2008*2008-........+2*2-1*1
tính 2010*2010-2009*2009+2008-.....+2*2-1*1
a) 2010/1+2009/2+2008/3+ ... +1/2010+2010 : 1+1/2+1/3+ ... +1/2010=
b) 1/2011+1/2010+1/2009+ ... +1/3+1/2 : 2010/1+2009/2+2008/3+ ... +1/2010=
Tính nhanh:
a,1/2009+2/2009+3/2009+......2008/2009
b,2010*2010*20092009-2009*2009*20102010/2009*20052005
a, \(\frac{1}{2009}+\frac{2}{2009}+...+\frac{2008}{2009}\\ \frac{\left(1+2008\right)\cdot2008\div2}{2009}=\frac{2017036}{2009}\)
Bài 2 : So sánh
A=2008/2009+2009+2010+2010+2011 và B=2008+20092+2010/2009+2010+2011
Tính tổng:
a,S1=1+(-2)+3+(-4)+..........+2009+(-2010)
b,S2=1+(-2)+(-3)+4+5+(-6)+(-7)+............+2008+2009+(-2010)
a,S1=1+(-2)+3+(-4)+..........+2009+(-2010)
S1=-1.(2010:2)
S1=-1005
b,S2=1+(-2)+(-3)+4+5+(-6)+(-7)+............+2008+2009+(-2010)
S2=-1.(2010:2)
S2=-1.1005
S2=-1005
Bài 2 : So sánh
\(A=\dfrac{2008}{2009}+\dfrac{2009}{2010}+\dfrac{2010}{2011}vàB=\dfrac{2008+2009+2010}{2009+2010+2011}\)
Ta có :
\(B=\frac{2008+2009+2010}{2009+2010+2011}=\frac{2008}{2009+2010+2011}+\frac{2009}{2009+2010+2011}+\frac{2010}{2009+2010+2011}\)
Vì :
\(\frac{2008}{2009}>\frac{2008}{2009+2010+2011}\)
\(\frac{2009}{2010}>\frac{2009}{2009+2010+2011}\)
\(\frac{2010}{2011}>\frac{2010}{2009+2010+2011}\)
Nên \(\frac{2008}{2009}+\frac{2009}{2010}+\frac{2010}{2011}>\frac{2008}{2009+2010+2011}+\frac{2009}{2009+2010+2011}+\frac{2010}{2009+2010+2011}\)
\(\Rightarrow\)\(A>B\)
Vậy \(A>B\)
Ta có: \(B=\frac{2008+2009+2010}{2009+2010+2011}\)
\(=\frac{2008}{2009+2010+2011}+\frac{2009}{2009+2010+2011}+\frac{2010}{2009+2010+2011}\)
Vì \(\frac{2008}{2009}>\frac{2008}{2009+2010+2011}\)
\(\frac{2009}{2010}>\frac{2009}{2009+2010+2011}\)
\(\frac{2010}{2011}>\frac{2010}{2009+2010+2011}\)
nên \(\frac{2008}{2009}+\frac{2009}{2010}+\frac{2010}{2011}>\frac{2008+2009+2010}{2009+2010+2011}\)
hay A > B
Vậy A > B
tính tổng sau :\(c=\frac{\frac{1}{2008}-\frac{1}{2009}-\frac{1}{2010}}{\frac{5}{2008}-\frac{5}{2009}-\frac{5}{2010}}+\)\(\frac{\frac{2}{2007}-\frac{2}{2008}-\frac{2}{2009}}{\frac{3}{2007}-\frac{3}{2008}-\frac{3}{2009}}\)
\(C=\frac{\frac{1}{2008}-\frac{1}{2009}-\frac{1}{2010}}{\frac{5}{2008}-\frac{5}{2009}-\frac{5}{2010}}+\frac{\frac{2}{2007}-\frac{2}{2008}-\frac{2}{2009}}{\frac{3}{2007}-\frac{3}{2008}-\frac{3}{2009}}\)
\(=\frac{\frac{1}{2008}-\frac{1}{2009}-\frac{1}{2010}}{5.\left(\frac{1}{2008}-\frac{1}{2009}-\frac{1}{2010}\right)}+\frac{2.\left(\frac{1}{2007}-\frac{1}{2008}-\frac{1}{2009}\right)}{3.\left(\frac{1}{2007}-\frac{1}{2008}-\frac{1}{2009}\right)}\)
\(=\frac{1}{5}+\frac{2}{3}\)
\(=\frac{13}{15}\)
Tính tổng sau
A=1-2+3-4+5-....-2008+2009
B=1+2-3-4+5+6-7-...-2007-2008+2009+2010
Bài làm:
\(A=1-2+3-4+5-...-2008+2009\)
\(A=\left(1-2\right)+\left(3-4\right)+\left(5-6\right)+...+\left(2007-2008\right)+2009\)
\(A=-1-1-1-...-1+2009\)(1004 số -1)
\(A=-1004+2009=1005\)
\(B=1+2-3-4+5+6-7-...-2007-2008+2009+2010\)
\(B=1+\left(2-3-4+5\right)+\left(6-7-8+9\right)+...+\left(2006-2007-2008+2009\right)+2010\)
\(B=1+0+0+...+0+2010\)
\(B=2011\)
Học tốt!!!!